2007
DOI: 10.1007/s11104-007-9311-8
|View full text |Cite
|
Sign up to set email alerts
|

Importance of point sources on regional nitrous oxide fluxes in semi-arid steppe of Inner Mongolia, China

Abstract: The aim of the present work was to estimate the contribution of different point and diffuse sources to the regional N 2 O emission strength of steppe in the Xilin river catchment, Inner Mongolia, People's Republic of China. Transect studies showed that the topographic effect on N 2 O emissions from upland soils was negligible and that upland steppe is only a very weak net source of N 2 O during the growing season (0.8 ± 0.4 mg N 2 O-N m À2 h À1 ). Slightly higher emissions were found for riparian areas (1.8 ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
32
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 41 publications
6
32
0
Order By: Relevance
“…Wang et al (2005a) suggested that soil moisture is the primary driving factor determining the spatial variability in N 2 O emissions from various semi-arid grassland types. Similar results were also reported by Corre et al (1996) for landscape N 2 O fluxes in the Black Soil Zone in Canada, and by Holst et al (2007b) for a landscape transect study in the Xilin River catchment. In our study, only less than 20% of the variance in N 2 O emissions could be explained by variations in WFPS or soil inorganic N contents alone.…”
Section: Patterns Magnitudes and Environmental Controls Of Ghg Fluxessupporting
confidence: 86%
See 3 more Smart Citations
“…Wang et al (2005a) suggested that soil moisture is the primary driving factor determining the spatial variability in N 2 O emissions from various semi-arid grassland types. Similar results were also reported by Corre et al (1996) for landscape N 2 O fluxes in the Black Soil Zone in Canada, and by Holst et al (2007b) for a landscape transect study in the Xilin River catchment. In our study, only less than 20% of the variance in N 2 O emissions could be explained by variations in WFPS or soil inorganic N contents alone.…”
Section: Patterns Magnitudes and Environmental Controls Of Ghg Fluxessupporting
confidence: 86%
“…The catchment comprises an area of 3,900 km 2 (Holst et al 2007b). Sampling sites were selected in the vicinity of the Inner Mongolia Grassland Ecosystem Research Station (IMGERS), Chinese Ecosystem Research Network (CERN).…”
Section: Site Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…Accumulation of carbon dioxide (CO 2 ) in the chamber enclosures has been identified as the major reason for overestimation in N 2 O emission quantification ). Thus, adding ascarite to the N 2 method (hereinafter referred to as the N 2 -Ascarite method), for removing CO 2 from the air samples, is one approach to avoid overestimation (e.g., Butterbach-Bahl et al 1997;Holst et al 2007Holst et al , 2008. By conducting two contrasting sets of measurements, using the N 2 and N 2 -Ascarite methods, Zheng et al (2008) have proposed correction terms for cropland N 2 O emission fluxes measured using the N 2 method.…”
Section: Gis Databasementioning
confidence: 99%